2006
DOI: 10.2741/1864
|View full text |Cite
|
Sign up to set email alerts
|

Germ cell apoptosis induced by experimental cryptorchidism is mediated by multiple molecular pathways in Cynomolgus Macaque

Abstract: Experimental cryptorchidism is a common model for examining the expression and function of heat-sensitive spermatogenesis-related genes in testis. Previous studies have shown that germ cells in cryptorchid testis die mainly in an apoptotic way. The molecular mechanism, however, is still unclear. We have established unilateral cryptorchid monkey model (Cynomolgus Macaque) to identify possible molecules involved in the germ cell apoptosis. The degree of germ cell apoptosis, the morphology of the cryptorchid test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 47 publications
3
15
0
Order By: Relevance
“…That is in agreement with previous observations in the testis of cryptorchid monkeys (Tao et al 2006) and in rat skeletal muscles after heat stress (Oishi et al 2002). In the present study, the expression level of HSP60 after the 9-week recovery period was still higher than that of the control.…”
Section: Discussionsupporting
confidence: 94%
“…That is in agreement with previous observations in the testis of cryptorchid monkeys (Tao et al 2006) and in rat skeletal muscles after heat stress (Oishi et al 2002). In the present study, the expression level of HSP60 after the 9-week recovery period was still higher than that of the control.…”
Section: Discussionsupporting
confidence: 94%
“…We previously demonstrated that heat‐induced germ cell apoptosis mainly occurred in spermatocytes and round spermatids, whereas spermatogonia were not sensitive to H in nonhuman primates (Zhou et al, 2002; Zhang et al, 2003a,b, 2005; Tao et al, 2006). Exogenous T was also capable of inducing germ cell apoptosis in monkeys (Zhou et al, 2001b; Lue et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These mice also confer partial resistance to heat‐induced germ cell apoptosis. Furthermore, germ cell apoptosis was dramatically increased in a time‐dependent manner after 43°C local treatment of monkey testes (Zhang et al, 2005) or experimental cryptorchidism (Tao et al, 2006). The number of apoptotic cells reached the maximum at day 8 and returned to the normal control level at the end of the recovery phase after 43°C warming (Zhang et al, 2005); this observation was consistent with the profile of changes in iNOS observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that the germ-cell loss associated with cryptorchidism in mammalian occurs by apoptosis, but the resultant mechanism has not been elucidated [2]. Interestingly, the balance between germ-cell proliferation and apoptosis in adults is also critical to control spermatogenesis [3].…”
Section: Introductionmentioning
confidence: 99%